Setting strategic agricultural research priorities based on potential impacts on poverty reduction: the case of Nigeria - Alene, Arega D.; Manyong, Victor M.; Tollens, E.F.; Abele, S. (2007)
Declining agricultural research budgets coupled with worsening poverty have increasingly required formal priority setting of public agricultural research in developing countries to ensure that scarce research resources are allocated in ways that will have the greatest impact on the poor. This paper assessed the potential impacts of alternative commodity research programs on poverty reduction and identified strategic agricultural research priorities in three agroecological zones of Nigeria. The paper discusses the poverty reduction-based priorities and their role in sharpening the focus of agricultural research to achieve poverty reduction objectives in Nigeria.